External voting: legal framework and overview of electoral legislation - Nohlen, Dieter; Grotz, Florian (Boletín mexicano de derecho comparado, 2000)
In a world order characterized by increasing migration, external voting has become highly significant. How can people living outside their country of origin have their political rights assured? Some have simply proposed that citizens living abroad ought to be entitled to vote in national elections. However, according to the authors of this essay, the notion of external voting as part of universal suffrage is neither self-evident nor unproblematic. After stating this, the article discusses a series of issues around external voting: the problem of political representation of citizens living abroad; the problem of judicial review of elections held on a foreign territory; and the problem of transparency of external voting procedures ...